CTO and Plastex paddle to Olympic glory using CFD simulation - Bugalski, T.; Kraskowski, M. (2009)
For most of the competitors at the 2008 Beijing Olympic Games, the possibility of mounting the podium to claim an Olympic medal represents the very pinnacle of sporting achievement: usually the payoff of many years of blood, sweat and tears. However, in 2008, being the best athlete is no longer necessarily enough: in most events the Gold Medal winner will also have had the aid of the very best sporting equipment. Author speaks about hydrodynamics and explains the simulations of the CTO and Plastex developments.